PENGARUH DESKRIPSI PEKERJAAN DAN FASILITAS TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. SAMUDRA PANGAN LESTARI MEDAN - Eldo Wijaya (Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
Work productivity essentially includes an attitude that always has the view that today's work methods must be better than yesterday's work methods and the work that can be achieved tomorrow must be more or of higher quality than the work achieved today. The job description does not discuss the problem of people or employees in the company, but issues regarding the scope of activities, basic functions, main tasks, job names, authorities, responsibilities, assessment criteria and also the results. Work facilities in principle focus on office or company work, namely helping to serve various activities or smooth work and also being a means of support in various company activities that are physical and can be used in normal company activities. This research uses quantitative descriptive research. The sampling technique used a saturated sample. The research scale used is a Likert scale.Partially, it was found that the job description variable had a significant effect on the work productivity of PT. Samudra Pangan Lestari. Partially it was found that the facility variable had a significant effect on the work productivity of PT. Samudra Pangan Lestari. Simultaneously there is a significant influence between the variable job description and facilities on the work productivity of employees of PT. Samudra Pangan Lestari